Abnormal dielectric properties and phase transition in Bi0.783(Mo0.65V0.35)O4 scheelite-related structured ceramic. Issue 25 (21st March 2015) - Zhou, Di; Li, Wen-Bo; Pang, Li-Xia; Yue, Zhen-Xing; Pang, Guang-Sheng; Yao, Xi
<x xml:space="preserve">Abstract</x> In the present work, an interesting phase transition at 150 °C in ordered scheelite structured Bi0.783(Mo0.65V0.35)O4 ceramic was observed for the first time.